Management of crizotinib therapy for ALK-rearranged non-small cell lung carcinoma: An expert consensus. Issue 2 (February 2015) - Cappuzzo, Federico; Moro-Sibilot, Denis; Gautschi, Oliver; Boleti, Ekaterini; Felip, Enriqueta; Groen, Harry J.M.; Germonpré, Paul; Meldgaard, Peter; Arriola, Edurne; Steele, Nicola; Fox, Jesme; Schnell, Patrick; et al.
Highlights Crizotinib is a standard of care for ALK-positive lung cancer. Crizotinib-associated AEs are mostly mild to moderate in severity. Appropriate monitoring and supportive therapies reduce the need for dosing modifications. Patients may have prolonged benefit from crizotinib after disease progression. Crizotinib should be continued for as long as the patient derives benefit.